Character Values of The Independent Learning Curriculum on The Profile of Pancasila Students in The Burlian Novel - Saifudin, Ahmad; Widiarini, Widiarini; Nafisatuzzahro', Nafisatuzzahro'; Utari, Utari; Musilawati, Fida Ayu (Universitas Nahdlatul Ulama Blitar, 2024)
In reality the profile of the Pancasila youth is still not maximally achieved. Based on data from the Indonesian Child Protection Commission, in 2020 the number of children victims of violence in schools (bullying) increased to 76 students from 46 students in the previous year. One of the legendary novels that holds a lot of values is the novel entitled Burlian by Tere Liye. This novel contains educational aspects that are relevant to everyday life. This study is to identify the character values in independent learning curriculum of profile of Pancasila students that can be implemented to build studentsâ€™ character in the novel â€œBurlianâ€. The research method is qualitative research with intertext approach. The role of the researcher is a compulsory because the researcher is the key instrument in this study. The